PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleracea L.) AKIBAT PEMBERIAN KOMPOS LIMBAH JAMUR TIRAM DAN PUPUK NPK - Moch Guntur Purnomo; Muharam Muharam; Rika Yayu Agustini (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
The Cauliflower (Brassica oleracea L.) PM 126 F1 is one of the vegetable commodities with a high enough demand because this vegetable is widely consumed by the public. This experiment purposes to get a dose combination of oyster mushroom waste organic fertilizer and NPK fertilizer which gives the highest growth and yield of cauliflower. The method of research used is the experimental method. The design of experimental used was randomize block design (RBD) with a single factor that consisted of 8 treatments with 3 replications, that is : A (control), B (10 ton/ha Organic fertilizer), C (20 ton/ha Organic fertilizer), D (30 ton/ha Organic fertilizer), E (NPK 800 kg/ha), F (10 ton/ha Organic fertilizer + NPK 800 kg/ha), G (20 ton/ha Organic fertilizer + NPK 800 kg/ha), H (30 ton/ha Organic fertilizer + NPK 800 kg/ha). the result highest curd weight is 7,75 ton/ha achieved by treatment G is 20 ton/ha waste compost of oyster mushroom and 800 kg/ha NPK fertilizer.